OPTIMASI PELAPISAN MATERIAL PEREDAM VISKOELASTIK PADA STRUKTUR PELAT ELASTIK - Suweca, I Wayan; Yusuf, Mokhamad Nuriman (Mesin, 2007)
This paper discusses a method to optimize the distribution of viscoelastic-damping layer on elastic plate structures. This method is based on well known SUMT (Sequential Unconstrained Minimization Technique) algorithm. An innovation where elementsâ strain energy distribution over the plate structure is used to determine the search direction vector. The method models the two layers damped plate as a single layer damped plate. The mechanical properties of single layer damped plate were determined such that they are equivalent to those of two-layers elasticviscoelastic laminate. MSC/Nastran finite element software was used to calculate the dynamic characteristics and the elementsâ strain energy distribution of the single layer plate. The proposed innovation has successfully determined the optimum distribution of viscoelastic material. The results show that the optimum distribution of viscoelastic material on elastic structure is strongly influenced by structural support type and number of modes retained for the analysis.